Analisis Faktor Pendorong Terjadinya Urbanisasi di Wilayah Perkotaan (Studi Kasus Wilayah Kota Makassar) - Syamsu Rijal; Thamrin Tahir (Journal of Economic Education and Entrepreneurship Studies, 2022)
The Indonesian state is experiencing increased development in big cities which can encourage the economy to grow. This attracted the attention of the villagers to seek their fortune in the city. However, urbanization events can have both good and bad impacts. Urbanization itself is divided into two types, namely permanent or permanent urbanization and temporary urbanization. The study of this study aims to determine the factors that drive urbanization in urban areas for a case study of the Makassar city area. In this case the researcher focuses on three main factors that are used as research benchmarks, namely the level of economic growth, employment opportunities, and education for their influence on the increase in urban society in the city of Makassar. From this research, it is found that the city of Makassar has an increasing level of economic growth and the availability of existing job opportunities so that the city of Makassar has a special attraction for people outside the city to enter looking for work or entrepreneurship, not only that, the availability of quality educational facilities and infrastructure in Makassar. The city of Makassar makes it a destination city for education or for continuing studies at a higher level so that it makes people, especially young people, to settle in Makassar City.